Fabrication of dimple structured surface of A390 Al-Si alloy using turning process - Mohd Dali, Mohd Nor Azam; Ghani, Jaharah A; Che Haron, Che Hassan; Hassan, Sharudin (Industrial lubrication and tribology, 2017)
Purpose The purpose of this paper is to produce dimple structure on a cylindrical surface for Aluminium-Silicon (Al-Si) alloy piston (A390) using turning process. The process selection is based on factors such as the capability of machining process, low cost process, minimum set up time and green working environment. Design/methodology/approach Three main machining parameters that greatly influenced the dimple structure fabrication were identified from previous researches (cutting parameters, vibration and cutting tool geometry). To facilitate dimple structure fabrication using turning process, a dynamic assisted tooling (DATT) was developed. Experiments were conducted on Al-Si A390 material for future application of automotive piston. A three-dimensional surface profiler (Alicona) was used for geometry measurement and analysis of dimple structure. The Taguchi method, with an L8 orthogonal array, was used to accommodate seven parameters used in the fabrication of dimpled structures using turning process. Signal-to-noise (S/N) ratio and observation on the shape of dimple structure array were used to determine the optimum machining condition. Findings Optimum parameters obtained using S/N ratio analysis were cutting speed of 9 m/min, depth of cut of 0.01 mm, amplitude displacement of 1 mm, nose radius of 0.4 mm and frequency of (25 Hertz). Whereas feed rate, rake and relief angles were not significant to the size, shape and dimple array; therefore, their selected values depend on requirement of the application. Based on the S/N ratio and uniformity of the array of dimple structure as the main reference, the sixth and eighth experiment conditions almost achieved the optimum condition which are able to produce the width of dimple structure of 396.82 and 560.43 μm, respectively, dimple length of 3,261.6 and 2,422.7 μm, respectively, dimple depth of 63.43 and 65.97 μm, respectively, area ratio of 10 and 10.39 per cent, respectively, and surface roughness of 3.0023 and 3.0054 μm, respectively. These results are within the range of dimple structure obtained by the previous researchers for sliding mechanical components application. Originality/value The optimum condition of machining parameters in producing uniform dimple structure led to the compilation of data base in dimple structure research via turning process. Dimple structure produced is similarly obtained with other processes like laser, burnishing, photochemical, etc. DATT developed has the ability to produce repeatable vibration frequency, stable and consistent amplitude displacement using a simple crank concept and structure that can be mounted on all types of lathe machine either conventional or computer numerical control.